THE ROLE OF RESERVE COMPONENT IN SUPPORTING TOTAL PEOPLE’S DEFENSE AND SECURITY SYSTEM (SISHANKAMRATA) TO CONFRONT THE THREAT OF THE SIXTH GENERATION WARFARE - Ryamizard Ryacudu; I Nengah Putra; Susilo Adi Purwantoro (The Republic of Indonesia Defense University, 2021)
The exponential growth of information and communication technology in this globalization era brings enormous changes to the new world order. This also shifts the warfare paradigm to a new generation. The traditional conventional threats (physically) have developed into multidimensional (physical and non-physical) ones. The Total People’s Defense and Security System (SISHANKAMRATA) adopted by the Indonesian is considered to be one of the most appropriate defense systems in confronting the threat of every war generation. The components of SISHANKAMRATA consist of the Indonesian National Military (TNI) as the main component and the National resources coming as the reserve and support component. Government Regulation Number 3 of 2021 concerning National Resource Management as a juridical basis regulating the components in the SISHANKAMRATA has just been passed. This study aims to explore the role of the reserve component as a national resource contributing to confronting the threat of the new generation of war; the sixth generation warfare. The method used in this study was a narrative analysis by developing literature studies, and previous researches. The results of this study confirm that the role of the reserve components is very important in SISHANKAMRATA facing the threat of modern warfare, including the sixth generation warfare.